Extracellular vesicles – A promising avenue for the detection and treatment of infectious diseases? - Fuhrmann, Gregor; Neuer, Anna Lena; Herrmann, Inge K. (European Journal of Pharmaceutics and Biopharmaceutics, 2017)
Extracellular vesicles (EVs) have gained increasing attention as novel disease biomarkers and as promising therapeutic agents. These cell-derived, phospholipid-based particles are present in many – if not all – physiological fluids. They have been shown to govern several physiological processes, such as cell-cell communication, but also to be involved in pathological conditions, for example tumour progression. In infectious diseases, EVs have been shown to induce host immune responses and to mediate transfer of virulence or resistance factors. Here, we discuss recent developments in using EVs as diagnostic tools for infectious diseases, the development of EV-based vaccines and the use of EVs as potential anti-infective entity. We illustrate how EV-based strategies could open a viable new avenue to tackle current challenges in the field of infections, including barrier penetration and growing resistance to antimicrobials.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Antibiotic resistance; Biosensing; Drug therapy; Exosomes; Immune response